Quality Control: An Effective Tool for Efficient Facility Operations and Maintenance Management in a Multi Campus Setting (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The study was an examination of quality control, an effective tool for Efficient Facility Operations and Maintenance Management in a Multi Campus Setting. The specific objectives were to determine if quality inspection, quality testing, quality repairs and quality replacement have significant impact on Efficient Facility Operations and Maintenance Management in a Multi Campus Setting. The study adopted a survey design which involved the administration of questionnaire instrument. Four research questions and hypotheses guided the study. The population of the study consisted of 114 staff of the university of Uyo while a sample size of 89 staff were selected through the taro- yame formular. Descriptive statistics was used to answer the research questions while the hypotheses was tested using the r2 value of regression analysis. The study showed that quality inspection, quality testing, quality repairs and quality replacement all have significant impact on Efficient Facility Operations and Maintenance Management in a Multi Campus Setting. Recommendation proffered include the need for policy on quality control, quality monitoring, quality inspection, quality replacement and quality repairs.